The Significance of the Country of Origin Principle for the Conflict of Laws Issue of Unfair Commercial Practices - Figura-Góralczyk, Edyta (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The article discusses the country of origin principle in the TFEU, the Unfair Commercial Practices Directive, the Directive on electronic commerce and the Polish regulations that implement them. The analysis allowed for the conclusion that the country of origin principle, as expressed in the TFEU, cannot indicate the applicable law. Art. 3 paragraphs 1 and 2 of the Directive on electronic commerce does not provide a basis to indicate the law applicable to unfair commercial practices, and nor does the Polish legislation implementing the Directive. These provisions have only such a meaning that at the stage of the application of law, determined by means of conflict of laws rules of Rome II Regulation, a court of a Member State undertakes an interpretation of the provisions of the applicable law, having regard to these provisions in such a manner so as not to restrict the provision of services for the information society in the internal market.